Computers and Society in the Past Half Century: The Conquest of Will Revisited - Mowshowitz, Abbe (Ethics International Press Limited, 2024)
Almost fifty years ago, the author wrote the first comprehensive critical study of social issues in computing, The Conquest of Will (1976). This new book revisits this seminal study, featuring an overview of technological advances over the past half century, and provides a unique comparison between what was believed and expected of computers back in 1976, and actual outcomes up to the present time. Despite the extraordinary changes in technology, much of what has emerged in contemporary society was anticipated fifty years ago, and we are still grappling with some of the same basic challenges. For example, the computer's threat to privacy has been a constant issue ever since the late 1950s, but the regulatory framework designed in the 1960s has been upended by the Internet. Artificial Intelligence too has been a contentious issue since the late 1950s, but until recently discussion was largely confined to academia, and there was little urgency to regulate its further development and application. The comparisons offered in this book will highlight what we got right and wrong in the past, and point to the sources of good and bad predictions. While there have been many studies of social issues in computing published since The Conquest of Will appeared in 1976, this is an unusual and valuable longitudinal comparison of the current situation with what prevailed and was predicted half a century ago.